2009
DOI: 10.1007/s11062-009-9078-z
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of EEG Related to Directed Perception and Analysis of Olfactory Information in Humans

Abstract: We recorded EEG in adult volunteers in the course of perception of smells of plant essential oils under conditions of directed attention. It was found that perception of olfactory information, even in the case of mild intensity of the smells inducing no aversive effects, correlates with noticeable changes in the EEG characteristics mostly typical of the reaction of nonspecific EEG activation induced by sensory stimulation and manifested in a decrease in the spectral power, SP, of low-frequency EEG components (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…However, high classification accuracy is also obtained in the occipital part of the brain (63.3%), although subjects were with eyes closed. Similar to Cherninskii et al [6], this may reflect the creation of mental visual images in the perception of odors. Finally, high classification accuracy in the frontal and the occipital regions indicates that EEG signals from these brain regions can be used for the discrimination and automatic recognition among hedonically different odors.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…However, high classification accuracy is also obtained in the occipital part of the brain (63.3%), although subjects were with eyes closed. Similar to Cherninskii et al [6], this may reflect the creation of mental visual images in the perception of odors. Finally, high classification accuracy in the frontal and the occipital regions indicates that EEG signals from these brain regions can be used for the discrimination and automatic recognition among hedonically different odors.…”
Section: Resultssupporting
confidence: 65%
“…However, other authors suggested that there are no changes in alpha activity but there are increases in theta activity [5]. Moreover, in a more recent study [6] a decrease in the activity of theta and alpha bands was found. In the same study, an increase in the high frequency EEG components (11-25 Hz) was reported.…”
Section: Introductionmentioning
confidence: 89%
“…However, other authors suggested that there are no changes in alpha activity but there are increases in theta activity [5,6]. Moreover, in a more recent study [7] a decrease in the spectral power of theta and alpha bands was found while smelling essential oils. In the same study, an increase in the high frequency EEG components (11-25 Hz) was reported.…”
Section: Introductionmentioning
confidence: 91%
“…In our previous study [1], we showed that directional perception of olfactory information in humans is accompanied by clearly pronounced rearrangements of EEG activity of the brain. In this case, naturally, it should be taken into account that modifications of the functional state of human cerebral systems related to perception of external sensory stimuli can, to a certain extent, correlate with psychophysiological parameters of the personality [2,3].…”
Section: Introductionmentioning
confidence: 81%
“…The technique of olfactory stimulation (more specifically, the technique of manipulations realized by the subject for perception of an odorant smell) was described in detail in our previous paper [1]. In the tested subjects, we recorded EEG before, in the course of, and after perception of the smells of different odorants, mostly plant essential oils (EOs).…”
Section: Methodsmentioning
confidence: 99%